THE ISOTOPIC SIGNATURE OF THE MINERALIZING FLUID OF THE LAVRION CARBONATE-REPLACEMENT PB-ZN-AG DISTRICT - Tombros, S.F.; Seymour, K.; Spry, P.G.; Bonsall, T.A (Bulletin of the Geological Society of Greece, 2010)
The Pb-Zn-Ag carbonate-replacement deposits in the Lavrion district are genetically related to a 7- 10 Ma-old granodiorite, felsic dikes and sills. These deposits are hosted in the Upper and Lower marble and schists of the Cyclades Blueschist unit and occur along the major Legraina detachment fault. Carbonate-replacement orebodies occur as “mantos” and veins, dominated by base metal sulfides and Ag, Bi, Sn, Sb, As, and Pb sulfosalts. Calculated carbon and oxygen isotope compositions of the hydrothermal fluid range from δ13CCO2 of -13.7 to 0.8 per mil and δ18OH2O of 4.2 to 27.4 per mil, at 400º, 350º, 320º, 300º, 250º and 200ºC. These isotopic compositions reveal water-torock ratios ranging from 4.8 to 52.6%, which reflect intense interaction of the ore fluid with the host rock in a water-dominated, transitional closed to open hydrothermal system. The range of δ34SH2S for sulfides in the deposits were from -8.5 to 6.8 per mil, for similar temperatures, whereas for barite-fluorite veins from δ34SH2S of -43.6 to -16.4 per mil, at 200º, 150º and 100ºC. This range implies that there was contribution from a magmatic sulfur component exsolved from the Plaka pluton, as well as contribution from a metasedimentary component. Based on the isotopic signature of sulfur for barite, the ranges from -6.7 to -7.6, comprising an increase in the fluid influx. Isotopic temperatures based on pyrite-galena and sphalerite-pyrite pairs revealed at least three major events of carbonate-replacement ore deposition, (i) at ~ 360º, (ii) 320º-280ºand (iii) 260º-200ºC.